2014
DOI: 10.1002/ejp.608
|View full text |Cite
|
Sign up to set email alerts
|

Gaze behaviour when monitoring pain faces: An eye‐tracking study

Abstract: We assume that initial vigilance for pain-associated stimuli might reflect an adaptive reaction to detect a potentially harmful stimulus. Subsequently, the pain-associated stimulus might be less attended for the purpose of mood regulation when all clear is given in this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 35 publications
(70 reference statements)
8
55
2
Order By: Relevance
“…Given the association between perceived injustice and pictorial ratings of sadness and anger (discussed below) a possible explanation for this non-significant finding may be that attention to cues of anger and sadness -rather than or in addition to pain per se -may be more salient. Indeed, a recent eye-tracking study [24] found that fear of pain (previously found to be associated with perceived injustice; [38,41]) tended to increase attentional preference to faces displaying anger.…”
Section: Discussionmentioning
confidence: 96%
“…Given the association between perceived injustice and pictorial ratings of sadness and anger (discussed below) a possible explanation for this non-significant finding may be that attention to cues of anger and sadness -rather than or in addition to pain per se -may be more salient. Indeed, a recent eye-tracking study [24] found that fear of pain (previously found to be associated with perceived injustice; [38,41]) tended to increase attentional preference to faces displaying anger.…”
Section: Discussionmentioning
confidence: 96%
“…For validation purpose, we now selected all those investigations, in which the PVAQ was related to the Pain Catastrophizing Scale (PCS) and the Pain Anxiety Symptom Scale (PASS) in order to be able to compute construct validity testing. This selection [15, 1726] resulted in a sample size of 617 healthy pain-free participants. Participants were recruited via advertisements posted in the university building or via advertisements in the local newspaper (Bamberg).…”
Section: Methodsmentioning
confidence: 99%
“…avoidance). The authors of these studies argued that there may be benefit to immediate orientation towards painrelated stimuli and, when that stimulus has no threat value, to disengaging from it quickly to maintain positive mood [28]. Other studies investigating the time-course of attentional processes have also found similar patterns of speeded orientation followed by avoidance [2].…”
Section: Figure 2 Near Here]mentioning
confidence: 99%